Analysis of Transformational Leadership and Organizational Culture and Influence on Job Satisfaction and its Implications on Employee Performance - Norawati, Suarni; Evita, Nora; Marantika, Abshor; Zakaria, Nurman (STMIK Widya Cipta Dharma, 2024)
Considering the bright prospects for food crop agriculture and horticulture, it is essential for the government to participate by planning, implementing, and fostering development in the agricultural sector. The goal is to increase agricultural production, thereby improving the income and welfare of farmers and the community. This research was conducted at the Department of Agriculture, Food Crops, and Horticulture, Kampar Regency. The aim of this study is to determine and analyze: the influence of transformational leadership on employee satisfaction; the influence of organizational culture on employee satisfaction; the direct influence of transformational leadership on employee performance; the direct influence of organizational culture on employee performance; the influence of job satisfaction on employee performance; the indirect influence of transformational leadership on employee performance through employee job satisfaction; and the indirect influence of organizational culture on employee performance through employee job satisfaction. This research utilized both primary and secondary data collected through questionnaires, interviews, observations, and documentation. The population consisted of all employees at the Department of Agriculture, Food Crops, and Horticulture in Kampar Regency, totaling 177 individuals. However, only 136 questionnaires were analyzed due to some being incomplete. Hypothesis testing was conducted using the Structural Equation Modeling (SEM) method with a 5% alpha level. The results of the study conclude that transformational leadership significantly influences employee job satisfaction, and organizational culture significantly influences employee job satisfaction. Transformational leadership has a direct and significant effect on employee performance, and organizational culture also has a direct and significant effect on employee performance. Job satisfaction significantly affects employee performance. However, transformational leadership does not have a significant indirect effect on employee performance through employee job satisfaction, whereas organizational culture does have a significant indirect effect on employee performance through employee job satisfaction.